HERMENEUTIKA AMINA WADUD SEBAGAI BASIS TAFSIR HARMONI ADIL GENDER DI INDONESIA - Said, Nur (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2017)
The domination of the interpretation of the Koran that tends to gender bias has been continued until now. Therefore the presence of Wadud as a feminist thinker to be interesting discussed. This article is to track the social and intellectual background that affect her points of views in term of tafsir and its relevance for developing feminist tafsir in Indonesia. This paper used the philosophical and hermeneutical approach. The data were collected by the method of documentation and discussed with the content analysis. The conclusions among others that Wadud has given a contribution in breaking down the traditional interpretation of the Koran by offering a critical approach to interpret  the Koran based on the awareness of  tauhid and analyse the preor-text in the interpretive process. This model of tafsir can be developed in Indonesian tafsir that still be dominated by male commentators, therefore in a certain level still become gender biased. It can be reproduced becoming an alternative feminist tafsir   to build harmony sociaty in Indonesia.